Assessing collision cross section calculations using MobCal-MPI with a variety of commonly used computational methods. (June 2021) - Ieritano, Christian; Hopkins, W. Scott
Graphical abstract: Highlights: MobCal-MPI computed ion collision cross sections (CCSs) in N2 were validated across 25 model chemistries. Computed CCSs are within 2–3 % of the experimental value for most model chemistries, indicating that any of the computational methods can be used with MobCal-MPI. A computational study of the [AT + βCD + H] + complex conducted at the PM7 and B3LYP-D3/6-31 G(d, p) level of theory shows that CCS agree with experiment within the expected error of the method (< 2.5 %). Abstract: Structural studies with ion mobility require an accurate methodology to bridge theoretical modelling of chemical structure with experimental determination of an ion's collision cross section (CCS). The parallelized MobCal-MPI package enables rapid and accurate evaluation of CCSs that are applicable to several chemical classes, but was only assessed for accuracy using a single model chemistry: B3LYP-D3/6-31++G(d, p). In this work, the performance of MobCal-MPI was validated across 25 different model chemistries, which encompassed PM7, Hartree-Fock, and three common DFT functionals (B3LYP-D3, ωB97X-D, and M06-2X-D3) using six different basis sets (6-31 G, 6-31 G(d, p), 6-31++G(d, p), def2-SVP, def2-TZVP, and def2-TZVPP). Performance assessment was accomplished using geometries generated from a set of 50 structurally diverse molecules at each level of theory. MobCal-MPI calculates CCSs that correlate well with experimental values for all model chemistries explored (< 2.5% RMSD) with the exception of PM7 (3.0 % RMSD) and methods that employ basis sets lacking polarization functions (e.g., 6-31G; < 4% RMSD). While any of the 25 model chemistries can be used with MobCal-MPI with reasonable accuracy, caution should be exercised when coupling CCS calculations with PM7 or basis sets that lack polarization functions. Following benchmarking, MobCal-MPI was used to calculate the CCS of a macromolecular construct consisting of atropine and β-cyclodextrin. The CCSs calculated for the β-cyclodextrin complex using either the PM7 or B3LYP-D3 model chemistries agree with experimental values within the expected error of the method (< 2.5 %).